Jember Fashion Carnival (JFC) as a Driver of Green Knowledge Spillover: A Literature Review - Yuliatin Azizah; Luxio Ximenes; Saiful Amin; Nely Supeni (ABM: International Journal of Administration, Business and Management, 2026)
This literature review examines the Jember Fashion Carnival (JFC) as a strategic driver for green product dissemination within the framework of the Knowledge Spillover Theory of Entrepreneurship. JFC, which began in 2003 as a small community initiative, has grown into an internationally recognized cultural event with a distinctive mandate requiring 30% recycled materials in costumes. The review synthesizes findings from academic journals, policy documents, and institutional reports to map how JFC functions as a knowledge source for green entrepreneurship. The analysis identifies three main dissemination mechanisms: (1) formal institutionalization of sustainability norms through mandatory recycling requirements, (2) community-based knowledge transmission through participatory event preparation, and (3) economic dissemination through collaboration of MSMEs (Micro, Small, and Medium Enterprises). The review concludes that JFC represents an emerging model in which cultural festivals can serve as intentional platforms for green knowledge diffusion, offering implications for creative economy policies in developing regions.